The impact of green supply chain practices towards operational performances among SMEs in Penang, Malaysia - Teoh, Bak Aun; Mohd Arzaman, Ameer Farhan; Chew, Boon Cheong; Abd Aziz, Mohd Syafiq; Kamalrudin, Massila (International Information and Engineering Technology Association, 2023)
This research aimed to examine the relationship between green supply chain practices and operational performance among small and medium enterprises (SMEs) in Penang, Malaysia. The practices of green supply chain in achieving operational performance have been a priority concern in Malaysia. Nevertheless, the concept of green supply chain practices adoption is in embryonic phase. The study used multiple regression analysis to investigate the green supply chain (GSC) practices and operational performance variables. The 120 self-administered questionnaires were randomly distributed among SMEs in Penang, Malaysia, with 59 responses collected. Theoretically, the research ascertained the positive relationship between GSC practices and operational performance variables. The findings align with the underlying theory of dynamic capabilities, which conceptualizes GSC practices and strategies to sustain operational performance within SMEs. In short, the findings of this research provided the research implications and recommendations to the researchers, industrial practitioners and policymakers who are having interest in these GSC practices and operational performance. This research served as a guideline for companies that tend to implement these GSC practices for improving its operational performance. The research revealed that both eco-design and packaging and reverse logistics practices are found to be significantly related to operational performance, but both green procurement and investment recovery practices found to be not significantly related to operational performance. There are gaps in the literature, hence, further research should be carried out on supply chain practices and operational performance. There are no fixed formulas for sustaining operational performance that match all conditions in Penang SMEs.